The Role of Hydrogen Sulfide in Renal System - Cao, Xu; Bian, Jin-Song (Frontiers in Pharmacology, 2016)
Hydrogen sulfide (H2S) has gained recognition as the third gaseous signaling molecule after nitric oxide (NO) and carbon monoxide (CO). This review surveys the emerging role of H2S in mammalian renal system, with emphasis on both renal physiology and diseases. H2S is produced redundantly by four pathways in kidney, indicating the abundance of this gaseous molecule in the organ. In physiological conditions, H2S was found to regulate the excretory function of the kidney possibly by the inhibitory effect on sodium transporters on renal tubular cells. Likewise, it also influences the release of renin from juxtaglomerular (JG) cells and thereby modulates blood pressure. A possible role of H2S as an oxygen sensor has also been discussed, especially at renal medulla. Alternation of H2S level has been implicated in various pathological conditions such as renal ischemia/reperfusion, obstructive nephropathy, diabetic nephropathy and hypertensive nephropathy. Moreover, H2S donors exhibit broad beneficial effects in renal diseases although a few conflicts need to be resolved. Further research reveals that multiple mechanisms are underlying the protective effects of H2S, including anti-inflammation, anti-oxidation and anti-apoptosis. In the review, several research directions are also proposed including the role of mitochondrial H2S in renal diseases, H2S delivery to kidney by targeting D-amino acid oxidase/3-mercaptopyruvate sulfurtransferase (DAO/3-MST) pathway, effect of drug-like H2S donors in kidney diseases and understanding the molecular mechanism of H2S. The completion of the studies in these directions will not only improves our understanding of renal H2S functions but may also be critical to translate H2S to be a new therapy for renal diseases.